O processo da educação social nas instituições de atendimento à criança e ao adolescente em situação de risco em Luanda: a experiência dos "Candengues Unidos" - Samba, Simão João (2007)
The present dissertation brings, in his content the discution of the process of social education in the institution of children and adolescent care in risk situation in Luanda. In Angola, especificaly the experience of the united Candegues association. Our main objective consist in understand and analise, from the interview to the director, educators, and adolescent from this institution, the activities and the education work developed by the institutions, the methodology and how the the developed work helps to fortify the family and social bonds, also the education the adolescent education of conscientious adolescent , independent, and capables of provide emanicipatory actions, aiming to build the identity of citizenship exercise. It was a study on the qualitative factors. To achieve the objectives, we appeal to the methodology of individual and focal group that consisted of four, 3 meeting. For better deeping of the thematic, we appeal to the literature of diverse areas of knowing like: sociology, economy, psychology, medicine and anthropology.The study showed that the process of the social education when understood well for the educators can provide trajectories of autonomy, emancipation and citizenship mainly to the children and adolescents in risk situations